PD-1 and PD-L1 expression in rare lung tumors - Marton Gyulai; Marton Gyulai; Zsolt Megyesfalvi; Zsolt Megyesfalvi; Zsolt Megyesfalvi; Lilla Reiniger; Tunde Harko; Bence Ferencz; Bence Ferencz; Luca Karsko; Laszlo Agocs; Laszlo Agocs; et al. (Frontiers Media S.A., 2023)
Background: Our knowledge is still limited about the characteristics and treatment of rare lung tumors. The aim of our study was to determine programmed cell death ligand-1 (PD-L1) and programmed cell death-1 (PD-1) expression in rare pulmonary tumors to assess the potential role of immunotherapy.Methods: 66 pathologically confirmed rare lung tumors including 26 mucoepidermoid carcinomas (MECs), 27 adenoid cystic carcinomas (ACCs), and 13 tracheobronchial papillomas (TBPs) were collected retrospectively. Immunohistochemical (IHC) staining was performed on formalin fixed paraffin embedded (FFPE) tumor tissues, and PD-L1 expression on tumor cells (TCs) and immune cells (ICs), and PD-1 expression on ICs were determined. The cut off value for positive immunostaining was set at 1% for all markers.Results: PD-L1 expression on TCs was observed in two cases of MEC (7.7%), one case of ACC (3.7%), and was absent in TBP samples. PD-L1 expression on ICs could be demonstrated in nine cases of MEC (34.6%), four cases of ACC (14.8%), and was absent in TBPs. All PD-L1 TC positive tumors were also PD-L1 IC positive. Higher expression level than 5% of PD-L1 TC and/or IC was observed only in one ACC and in two MEC patients. Among them, strong PD-L1 immunopositivity of >50% on TCs and of >10% on ICs could be demonstrated in one MEC sample. PD-L1 expression of ≥1% on ICs was significantly more common in MEC, than in TBP (p < 0.001). In MEC ≥1% PD-L1 TC or IC expressions were significantly more common in patients aged 55 or older, than in younger patients (p = 0.046, and p = 0.01, respectively). PD-1 expression on ICs was found in five cases of MEC (19.2%), four cases of ACC (14.8%), and in two cases of TBP (15.4%). Only one MEC case showed a higher than 5% expression level of PD-1 on ICs.Conclusion: This retrospective study comprehensively demonstrated the rare expression of PD-L1 and PD-1 in pulmonary MEC, ACC, and TBP. However, we found very strong PD-L1 immunopositivity on both TCs and ICs in one MEC sample, which warrants further investigations in a larger cohort.